Total Delay in Treatment of Tuberculosis and Associated Factors among New Pulmonary TB Patients in Selected Health Facilities of Gedeo Zone, Southern Ethiopia, 2017/18. (2nd June 2019) - Awoke, Netsanet; Dulo, Bedado; Wudneh, Feven
Abstract : Background . TB is an infectious disease caused by the bacillus Mycobacterium TB complex. It is a major public health concern causing devastating illness in millions of people each year and one of the top 10 causes of death worldwide following HIV pandemic. It demands huge costs each year for prevention, diagnosis, and treatment of TB. Global TB control progress depends on major advances in early diagnosis and treatment. Despite progress in providing diagnosis and preventive treatment of TB, big detection and treatment gaps remained with delayed diagnosis and treatment of TB especially in resource-limited countries. This is mainly because of factors related to the patient and health care system including sociodemographic, economic, and cultural barriers to accessing TB care. Objective . The study conducted in Gedeo Zone, Southern Ethiopia, had the primary purpose of identifying the median delay in starting a correct TB treatment and the associated factors for such a delay in patients newly diagnosed with PTB in selected health facilities of Gedeo Zone, Southern Ethiopia, 2017/18. Methods . Institutional based cross-sectional study was conducted among new pulmonary TB patients in selected health institution of Gedeo Zone, Southern Ethiopia, 2017, from October, 2017, to May, 2018. All new pulmonary TB patients who fulfill the inclusion criteria during the study period were included in the study after informed consent was obtained from the participants. Data was cleaned, coded, and entered into SPSS version 20 for analysis. A frequency for variables was calculated. Chi-square was used to screen the possible potential associated factors and multivariate analysis was used to ascertain the association between variables. All statistical tests values of p<0.05 were considered as statistically significant. Result . The median total in treatment of TB was 60 days. Among the total study participants, 50.9% of the participants have unacceptable/longer total delay in TB treatment. Being of female gender, not attending formal education, having rural residency, having poor knowledge of TB, having home distance >10Km from the nearest health facility, visiting nonformal health care provider, and taking antibiotic treatment before TB diagnosis empirically were identified as significant independently associated factors for unacceptable total treatment in TB. Conclusions . There was higher median total delay in treatment of TB (60 days) and an overall prevalence of 50.9% unacceptable/longer total delay in treatment of TB. Female gender, rural residence, not attending formal education, visiting nonformal health facility as first health care seeking, having poor knowledge of TB, and having antibiotic treatment before TB diagnosis were identified as independent significant associated factors.